2017
DOI: 10.1051/ocl/2017041
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of mango seed kernel oil extraction using response surface methodology

Abstract: -Response surface methodology (RSM) was applied to study the optimum condition of mango seed kernel oil (MSKO) extraction with n-hexane. In the present paper, for the first time, we provide an optimal condition of MSKO extraction to obtain the maximum of yield, total phenolic content (TPC) and vitamin E. The experiment was conducted using central composite design (CCD) consisted of twenty experimental points including six replicates of center points to study the effect of three independent variables: temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
1
13
0
1
Order By: Relevance
“…Malaysian Harumanis had higher total fat content than that of Indonesian Harumanis variety (7.03%) that has been extracted under optimized conditions by Mas'ud, Mahendradatta, Laga, and Zainal (2017). The variation could be due to the differences in the seasonal, climatic, maturity of the fruit, and geological conditions between the two countries (Jahurul et al, 2014).…”
Section: Total Weight Seed Kernel and Fat Contentsmentioning
confidence: 92%
See 1 more Smart Citation
“…Malaysian Harumanis had higher total fat content than that of Indonesian Harumanis variety (7.03%) that has been extracted under optimized conditions by Mas'ud, Mahendradatta, Laga, and Zainal (2017). The variation could be due to the differences in the seasonal, climatic, maturity of the fruit, and geological conditions between the two countries (Jahurul et al, 2014).…”
Section: Total Weight Seed Kernel and Fat Contentsmentioning
confidence: 92%
“…The MKFs from the three varieties also had similar IV with palm oil (47.0-55.8 g I 2 /100 g) (Li et al, 2012) and were in the range of shea butter (36.6-65.0 g I 2 /100 g) (Adomako, 1977;Gunstone et al, 1994;Honfo, Akissoe, Linnemann, Soumanou, & Van Boekel, 2013) but higher than cocoa butter (34.0-38.4 g I 2 /100 g) (Jahurul et al, 2019), illipe butter (23.0-38.0 g I 2 /100 g) (Minifie, 2012;Rahman, Basri, Rahman, Rahman, & Salleh, 2011), and sal butter (32.1-41.0 g I 2 /100 g) (Kumar et al, 2016). These fats have low IV implied that they have higher content of saturated fatty acids, higher degree of hardness, better oxidation resistance, and greater storage stability than the MKFs (Mas'ud et al, 2017). The IV of the MKFs should be reduced in order to improve its suitability as CBE.…”
Section: Iodine Valuementioning
confidence: 99%
“…3, where the lack of fit represents other contributions of the higher order terms. A significant lack of fit generally shows that the model failed to represent the data in the experimental domain at which points were not included in the regression [33]. All SOP models had an insignificant lack of fit tests, which means that all the models represented the data satisfactorily.…”
Section: Response Surface Methodologymentioning
confidence: 99%
“…In the extraction process, an optimum point will be reached. Mas'ud et al (2017) conducted a study of the effects of extraction time, temperature, and volume of solvent in mango seed kernel oil extraction above room temperature, they reported that the variables had a significant effect on oil yield. Effect of the combination of reactions between variable time and temperature at high-level experimental process will obviously result in a decrease in oil yield.…”
Section: Extraction Yield Of Rbomentioning
confidence: 99%